Batroxobin in combination with anticoagulation may promote venous sinus recanalization in cerebral venous thrombosis: A real‐world experience. (23rd January 2019) - Ding, Jia‐Yue; Pan, Li‐Qun; Hu, Yan‐Yu; Rajah, Gary B.; Zhou, Da; Bai, Chao‐Bo; Ya, Jing‐Yuan; Wang, Zhong‐Ao; Jin, Ke‐Xin; Guan, Jing‐Wei; Ding, Yu‐Chuan; Ji, Xun‐Ming; et al.
Summary: Aims: The objective of this study was to evaluate cerebral venous recanalization with magnetic resonance black‐blood thrombus imaging (MRBTI) in patients with cerebral venous thrombosis (CVT) who underwent batroxobin treatment in combination with anticoagulation. Methods: A total of 31 CVT patients were enrolled in this real‐world registry study. The patients were divided into batroxobin (n = 21) and control groups (n = 10). In addition to the same standard anticoagulation as in the control group, patients in the batroxobin group underwent intravenous batroxobin for a total of three times. Results: In the batroxobin group compared with the control group, we found better odds of recanalization degree [adjusted OR (95%CI) of 8.10 (1.61‐40.7)] and segment‐stenosis attenuation [adjusted OR (95%CI) of 4.48 (1.69‐11.9)] with batroxobin treatment. We further noted a higher ratio of patients with the attenuation of stenosis [adjusted OR (95%CI) of 26.4 (1.10‐635)]; as well as a higher ratio of segments with stenosis reversion [adjusted OR (95%CI) of 4.52 (1.48‐13.8)]. However, neurological deficits between the two groups showed no statistical difference at 90‐day follow‐up ( P > 0.05). Conclusions: Batroxobin may promote venous sinus recanalization and attenuate CVT‐induced stenosis. Further randomized study of this promising drug may be warranted to better delineate the amount of benefit.